Physiochemical characterization of a potential Klebsiella phage MKP-1 and analysis of its application in reducing biofilm formation - Das, Sayani; Kaledhonkar, Sandip (Frontiers in Microbiology, 2024)
The common intestinal pathogen Klebsiella pneumoniae (K. pneumoniae), is one of the leading causes of fatal superbug infections that can resist the effects of commonly prescribed medicines. The uncontrolled use or misuse of antibiotics has increased the prevalence of drugresistant K. pneumoniae strains in the environment. In the quest to search for alternative therapeutics for treating these drug-resistant infections, bacteriophages (bacterial viruses) emerged as potential candidates to be used in phage therapy against Klebsiella. The effective formulation of phage therapy against drug-resistant Klebsiella infections demands thorough characterization and screening of many bacteriophages. To contribute effectively to the formulation of successful phage therapy against superbug infections by K. pneumoniae, this study includes the isolation and characterization of a novel lytic bacteriophage MKP-1 to consider its potential to be used as therapeutics in treating drug-resistant Klebsiella infections.Morphologically, having a capsid attached to a long non-contractile tail, it was found to be a siphovirus that belongs to the class Caudoviricetes and showed infectivity against different strains of the target host bacterium. Comparatively, this double-stranded DNA phage has a large burst size and is quite stable in various physiological conditions. More interestingly, it has the potential to degrade the tough biofilms formed by K. pneumoniae (Klebsiella pneumoniae subsp. pneumoniae (Schroeter) Trevisan [ATCC 15380]) significantly. Thus, the following study would contribute effectively to considering phage MKP-1 as a potential candidate for phage therapy against Klebsiella infection.